De burger als eunuch - N.C.F. van Sas (BMGN: Low Countries Historical Review, 2002)
'1800. Blueprints for a society' argues the case for the primacy of culture in late 18th-century Dutch society. Drawing upon the work of a generation of dix-huitiémistes it presents an impressive and highly readable overview of the Dutch Enlightenment. Unfortunately, this cultural vantage-point also results in a rather one-sided, if not positively unhistorical reading of this period which — by all accounts so far — was highly charged with politics. In fact, an opportunity is missed to connect the Enlightened civil society of the 1760s and 1770s with the revolutionary developments of the 1780s and 1790s.